Age-associated losses of brain volume predict longitudinal cognitive declines over 8 to 20 years. - Rabbitt, P; Ibrahim, S; Lunn, M; Scott, M; Thacker, N; Hutchinson, C; Horan, M; Pendleton, N; Jackson, A (2008)
Absolute differences in global brain volume predict differences in cognitive ability among healthy older adults. However, absolute differences confound lifelong differences in brain size with amounts of age-related shrinkage. Measurements of cerebrospinal fluid (CSF) volume were made to estimate age-related shrinkage in 93 healthy volunteers aged 63 to 86 years. Their current levels of brain shrinkage predicted their amounts of decline over the previous 8 to 20 years on repeated assessments during a longitudinal study on the Cattell "Culture Fair" Intelligence Test, on two tests of information processing speed, and marginally on the Wechsler Adult Intelligence Scale (D. Wechsler, 1981), but not on three memory tests. Loss of brain volume is an effective marker both for current cognitive status and for amounts and rates of previous age-related cognitive losses.